Methylation Analysis of Rb, P16, MGMT, and hMLH-1in Mucoepidermoid Carcinomas. A Pilot Study - Martínez-Marcial, Luis A.; Jacinto-Alemán, Luis F.; Trejo-Remigio, David A.; Ramírez-Martínez, Carla M.; Leyva-Huerta, Elba R. (Odovtos - International Journal of Dental Sciences, 2023)
Mucoepidermoid carcinoma (MC) is the most common malignant epithelial neoplasm in the salivary glands. This neoplasm has varying proportions of mucous, epidermoid, intermediate, columnar, and clear cells. MCs have been associated with CRTC1-MAML2 genes; however, their pathogenesis is uncertain. Recently, epigenetic changes have been considered a possible aetiologic factor. To identify the methylation state of RB, P16, MGMT, and hMLH genes in the three severity grades of MC were used five MCs and one healthy minor salivary gland as a control group (CG) obtained from the Pathology and Oral Medicine Laboratory and analyzed using MS-PCR to compare the presence or absence of methylation in promotor regions. The Kruskal-Wallis test was performed, with p≤0.05 considered significant. CG was employed as the normalizer of methylation levels. All assays were performed in triplicate. The mean age of our population was 52.6±18.6 years old; the total population was female and included 2 low grade, 2 intermediate grade, and 1 high grade levels of severity. When comparing the methylation status of the three histopathological grades of MC against the control, statistically significant differences were observed in Rb-M, MGMT-M, and hMLH-1-NM for high-grade severity, with p values of 0.03, 0.05, and 0.04, respectively. Methylation is a possible mechanism for pathogenesis processing of high-grade MC. However, a larger sample population is necessary to validate this finding.